Correctional administration and change management - Hurley, Martha Henderson (CRC Press, 2010)
Change is an inevitable part of any correctional institution, as new trends and initiatives constantly bombard the system. However, as budgetary constraints increasingly require correctional agencies to do more with less, a paradigm shift in the way they operate is imperative to ensure success. Correctional Administration and Change Management examines leadership, management, and organizational culture and how they apply to correctional agencies, enabling administrators to identify the changes that can be successfully implemented within the organizational context. The book begins by defining th.